Pengaruh Fasilitas dan Intelektualitas terhadap Implementasi Kinerja Pegawai Bank Syariah Mandiri KCP Cimone Tangerang Periode 2019 - Muhammad Sopiyana; Septian Arief Budiman (Universitas Pamulang, 2020)
Bank Syariah Mandiri KCP Cimone Tangerang is a bank that uses sharia principles and a bank that constantly strive to improve employee work productivity so that the performance provided to customers is maximal to support the success of service quality and attractive and profitable performance quality. One of the bank's assessments is said to be good if the employee's work productivity is good, both from service to customers and the internal parties of the bank. Also always provide facilities and intellectuality to the implementation to its employees. Employees often do not understand their duties, and the knowledge of employees is still low on the function of intellectual facilities to the implementation of their performance. This makes the work system less effective and there are still employees who need training and education to further improve the quality of employees. How important facilities and intelligence factors to the implementation of employee performance in carrying out their duties, so that it will be more productive. The type of research used in this research is quantitative with associative research properties. Associative research is a study that aims to find out the relationship between two or more variables. The research location is at Bank Syariah Mandiri KCP Cimone. The population and samples using tenik purposive sampling from this study were employees of Bank Syariah Mandiri KCP Cimone Tangerang. The data collection technique is using questionnaires, interviews, and observations. Data analysis techniques use classic assumption tests and multiple linear regressions with SPSS 23 applications. The results of the research are Facilities Affecting Employee Performance Productivity, Intellectuality is very influential on employee performance, and In simultaneously both variables namely facilities and intellectuals can affect the implementation of employee performance of Bank Mandiri Syariah Keywords: Facilities, Intellectuality, Implementation